2019
DOI: 10.3390/cells8101275
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin Targets tNOX (ENOX2) to Inhibit G1 Cyclin/CDK Complex, as Assessed by the Cellular Thermal Shift Assay (CETSA)

Abstract: Capsaicin (8-methyl-N-vanillyl-6-noneamide), which is an active component in red chili peppers, is used as a chemopreventive agent that shows favorable cytotoxicity against cancer cells. Accumulating evidence indicates that capsaicin preferentially inhibits a tumor-associated NADH oxidase (tNOX, ENOX2) that is ubiquitously expressed in cancer but not in non-transformed cells. This attenuates cancer cell growth by inducing apoptosis. The capsaicin-mediated inhibition of tNOX was recently shown to prolong the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 40 publications
3
17
0
Order By: Relevance
“…Moreover, both APP-CTFs (α- and β) behaved similarly upon temperature exposure while APP-βCTF levels were not influenced by the presence of a binding ligand either. Other commonly used loading controls, vinculin, β-actin, GAPDH, HSP70 and SOD-1, all exhibited temperature sensitivities in our study, as previously reported 7 11 . By means of example, we validated the use of APP-αCTF as a CETSA loading control for the kinase, MEK (mitogen-activated protein kinase kinase), in the presence of two inhibitors using the wild-type HEK293 cell line.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, both APP-CTFs (α- and β) behaved similarly upon temperature exposure while APP-βCTF levels were not influenced by the presence of a binding ligand either. Other commonly used loading controls, vinculin, β-actin, GAPDH, HSP70 and SOD-1, all exhibited temperature sensitivities in our study, as previously reported 7 11 . By means of example, we validated the use of APP-αCTF as a CETSA loading control for the kinase, MEK (mitogen-activated protein kinase kinase), in the presence of two inhibitors using the wild-type HEK293 cell line.…”
Section: Introductionsupporting
confidence: 85%
“…Traditional qWB loading controls have been utilised previously but are ill-suited for this unintended purpose. Vinculin, β-actin, GAPDH, α-tubulin and even heat-shock chaperone 70 (HSP70) decrease in concentration as temperature increases 7 11 . Superoxide dismutase-1 (SOD-1), a promising candidate owing to its reported stable range of 35–95 °C 12 14 , was found to transition through different unfolded states with increasing temperature 13 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…In BC, CPS triggers the proteasomal degradation of tNOX, leading to the inhibition of NAD+-dependent SIRT1 deacetylase and the enhancement of c-Myc and p53 that suppresses G1 cyclin-dependent kinase activation and triggers cell cycle arrest [ 14 ]. Moreover, by downregulating SIRT1, CPS enhances the acetylation of cortactin and β-catenin to decrease MMP-2 and MMP-9 activation and impair cell migration in BC cells [ 15 , 16 ]. CPS suppresses cell proliferation, and induces cell cycle arrest and reactive oxygen species (ROS) production in BC cells, through FOXO3a-mediated pathways [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Atikul et al used the CETSA technology to verify the binding of capsaicin to the cell cycle-related enzyme tNOX, and found that capsaicin can bind to tNOX in T24 bladder cancer cells. This combination inhibits the production of NAD+ and down-regulates tNOX, thereby inhibiting sirtuin-1 (SIRT1) deacetylase activity [93]. Ultimately, decreased SIRT1 deacetylase activity will enhance the acetylation of c-Myc and p53, leading to cell cycle arrest, thereby inhibiting the growth of cancer cells.…”
Section: Cellular Thermal Shift Assaymentioning
confidence: 99%